Role of F-18 FDG PET/CT in assessing IgG4-related disease with inflammation of head and neck glands - Tokue, Azusa; Higuchi, Tetsuya; Arisaka, Yukiko; Nakajima, Takahito; Tokue, Hiroyuki; Tsushima, Yoshito (Annals of nuclear medicine, 2015)
Purpose The aim of the current study was to evaluate the utility of F-18-fluoro-2-deoxy- d -glucose (F-18 FDG) positron emission tomography/computed tomography (PET/CT) in assessing patients diagnosed with immunoglobulin G4 (IgG4)-related disease (IgG4-RD) with inflammation of the head and neck glands. Methods We reviewed the records of 17 patients (16 men and 1 woman) with IgG4-RD exhibiting inflammation of the head and neck glands (lacrimal or salivary glands; LSG) who were diagnosed by excisional biopsy of the LSG. F-18 FDG PET/CT images were retrospectively evaluated for locations of high FDG accumulation, and the maximum standardized uptake value (SUV max ) of each lesion was calculated. Results In 15 of 17 patients (88 %), FDG accumulation was observed in organs outside of the biopsied LSG. High FDG accumulation was most frequently seen in the lymph node (71 %), followed by the non-biopsied LSG (41 %). FDG accumulation was also found in other typically affected organs including the prostate and retroperitoneum (18 %), kidney and lung (12 %), and pancreas (1 %). FDG accumulation was most commonly observed in two lesions outside of the biopsied site (41 %). Conclusions Detection of the multi-organ involvement before treatment is important for patients with IgG4-RD. F-18 FDG PET/CT is an effective tool for assessing the location of extra-LSG lesions in patients with IgG4-RD with LSG inflammation.